Pengaruh Komposisi Media Tanam dan Pemberian Limbah Cair Pabrik Kelapa Sawit Kolam Aerob Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pre-Nursery - Firman K. Manurung; Jonatan Ginting; Toga Simanungkalit (Jurnal Agroekoteknologi, 2014)
The availability of top soil as an oil palm sead plant media is very limited, so to contend it is usedsub soil plant media which more available and easier to get it, but it has bad chemicalcharacteristics. Application Oil Palm Empty Bunch (OPEB) compost or Palm Oil Liquid Waste ofaerobic pond is expected to bost growth of Palm Seed (Elaeis guineensis Jacq.).This research hadbeen conducted at Net House of Agriculture Faculty, North Sumatera University in October 2013until January 2014,, using factorial randomized block design with two factor i.e. composition ofplanting media (90% Sub-soil + 10% OPEB compost, 80% Sub-soil + 20% OPEB compost, 70%Sub-soil + 30% OPEB compost, and 100% Top-soil) and Palm Oil Liquid Waste (0, 1, 2, and 3litre/plant).Parameter observed were plant’s height, stem diameter, number of leaf, total leaf area,volume of root, upper part fresh weight, root weight, upper part dry weight, dry root weight. Theresult showed composition of planting media on palm seed give no real effect to all of parameterobserved.Application of Oil Palm Liquid Waste significantly affect the parameter number of upperpart fresh weight and root weight. Interaction of both do not give a real effect to all of parameterobserved. The best result from this experimental were obtained in the treatment of compositionplanting media at 70% Sub-soil + 30 OPEB compost and application of Palm Oil Liquid Waste at 3litre/plant.Keywords: Planting Media, Palm Oil Liquid Waste, Oil Palm Seed